Evaluation of the Juvenile Breaking the Cycle Program in Lane County, Oregon, 2000-2002 - Lattimore, Pamela K. ([Verlag nicht ermittelbar], 2006)
This study was conducted between April 15, 2000 and November 15, 2002 to evaluate the effects of the Juvenile Break the Cycle program (JBTC) in Lane County, Oregon on the interim and longer-term outcomes for juvenile offenders who were deemed high risk and had a history of alcohol and/or other drug use. The study was conducted using three waves of interviews as well as administrative data. The baseline interview was given to and administrative data were collected on 306 juveniles. The 6-month follow-up interview was completed by 208 juveniles and the 12-month follow-up interview was completed by 183 juveniles. Variables included in the study are history of alcohol and/or other drug use, diagnosis of mental health problems, history of previous contact with the juvenile justice system, substance abuse risk score, total risk score, and history of substance abuse treatment or mental health counseling. Variables related to JBTC include program assignment, the number of drug test administered between interviews, and the number of positive drug tests.